Benefits and issues of education program for nurse-midwives on milk expression care for preterm mothers in postpartum period. Issue 10 (October 2022) - Tanaka, Rie; Horiuchi, Shigeko
Abstract: Background and aims: Breastfeeding is important for preterm mothers and infants. However, evidence-based practice and standardized education remain inadequate. To implement evidence-based practice, continuous education is mandatory for nurse-midwives. We previously implemented our developed education program on early essential milk expression care for preterm mothers among Japanese nurse-midwives. Herein, we aimed to assess the effects of our education program on nurse-midwives' knowledge of milk expression care for preterm mothers in terms of changes in their correct answer rates for 20 specific knowledge items before and after the education program implementation. We also aimed to identify program-related issues from nurse-midwives' comments to improve the program. Methods: We conducted a secondary analysis of our previous data and surveyed the knowledge of 36 nurse-midwives who received a similar face-to-face education program on milk expression care for mothers three months before (Pre-1), just before (Pre-2), just after (Post-1), and three months after (Post-2) the program. We obtained their comments at Post-2 and identified issues for program improvement. Results: The knowledge items, in which the correct answer rates of Post-1 were significantly higher than those of Pre-2, were Verification of the motivation and intent, Benefits of breastfeeding for mothers and infants, Milk volume on the fourth day and at around the second week after birth, Lactogenesis stage 3, Autocrine control, Time between birth and the initiation of milk expression, Early initiation of milk expression, Frequent milk expression, and Duration of pumping. The issues identified were practical training, knowledge retention, and misunderstanding knowledge. Conclusions: Nurse-midwives' unacquired knowledge of milk expression care for preterm mothers was effectively supplemented by the education program. Pre-education knowledge items with low correct answer rates must be strengthened during in-service education. Practical training, knowledge retention, and misunderstanding knowledge can be improved. Abstract : Preterm birth; Breast milk expression; Obstetric nursing; Knowledge; Education program.